Endoscopic Therapy for Barrett's Esophagus - Sampliner, Richard E. (Clinical Gastroenterology, 2009)
Endoscopic Therapy is emerging as the preferred therapy for early neoplasia in Barrett's Esophagus. This volume provides the key decision making factors in determining endoscopic therapy for an individual patient. All current techniques and complications of ET are provided including, photodynamic therapy (PDT), APC, multipolar electrocoagulation (MPEC), RF, ER, and cryotherapy. Each technique includes "how to highlights", high quality color endoscopic images, line drawings and diagrams. Endoscopic imaging modalities to detect dysplasia, decision making in the clinical arena and cost-effectiveness of ablation are some of the additional topics discussed in this highly practical volume. Written by experts in the field of endoscopic therapy, this text educates GI practitioners and researchers about this under-utilized approach to the treatment of Barrett's Esophagus.